Peran Media Sosial Dalam Meningkatkan Minat Berwirausaha Mahasiswa - Tyo Rizky Siagian (Global Leadership Organizational Research in Management, 2024)
This research aims to find out the role of social media in increasing the entrepreneurial interest of students in the management study program, Faculty of Islamic Economics and Business, North Sumatra State Islamic University. This research uses qualitative research methods. The results of this research are that social media is found to really help students in carrying out entrepreneurial activity and also makes it easier because it can reach a wider market, not only the campus environment but can also reach the environment outside the campus. Apart from that, by utilizing technological developments, namely social media, students become confident when marketing goods to be sold because they market their merchandise online.